The effect of varying danger controllability on attention to threat messages. Issue 2 (9th January 2020) - Herbert, Matthew; Notebaert, Lies; Parsons, Sam; Fox, Elaine; MacLeod, Colin
Summary: The objective of this study is to determine whether attention toward fear messages is affected by variation in the controllability of the associated danger. There is no consensus regarding the effectiveness of fear appeals in driving adaptive behaviour, and it may be the case that threat messages fail to capture attention if the associated danger is not explicitly controllable. One hundred and sixty undergraduate university students completed a computer task that involved exposure to threat cues signalling a danger (money loss). In high control blocks, attending to threat cues provided a high chance of avoiding the danger, whereas in low control blocks, attending to threat cues provided little chance of avoiding the danger. Attentional capture by threat was measured. A mixed‐design analysis of variance showed there was greater attentional capture by threat cues in high control blocks compared with low control blocks. This effect was observed with a short stimulus exposure duration and was magnified with a long exposure duration. Fear appeals could capture attention to a greater degree if the danger related to the threat message was communicated as being controllable. This has significant practical implications for the implementation of fear appeals.